PENERAPAN PEMBELAJARAN MODELLEARNING CYCLE DALAM MENINGKATKAN MINAT DAN HASIL BELAJAR AKUNTANSI POKOK BAHASAN JURNAL PENYESUAIAN PADA KELAS XI IPS 3 DI SMAN 4 BARABAI - Ita Sari (Universitas Lambung Mangkurat, 2016)
The subject of Economy, specially Accountancy major was the most important lesson in life and for the students it can raise curiosity, fairness, hard work, dicipline and creative and innovative interpreneurship. The problem which is faced nowadays is that economy/accountancy with the main topic Journal of Adaptation is percepived as the difficult lesson for some students. In addition, the teachers do not implement learning model maximally, as the consequence of this condition causes students have less interest in studying it and the result of studying is low. In this research the aspects studied were student learning activity, student’s interest, studying result and student response by using Learning Cycle Model in Accountancy lesson with main topic Journal of Adaptation. This research is a classroom action research with quatitaive approach. The result of this reseach shows that student learning activity increased; in cycle I was 3,20 (not good ) and in cycle II became 4 (good ); students’ interest in learning at cycle II was 49,74 % (enough) in second II became 98,05 (very good). The result of studying in cycle II was 78,96 and in cycle II increased became 85,45. The completeness in cycle I was 21 % and in cycle II was 100%. From response using questionnaire it is stated 75,8% of students agreed and liked Learning Cycle Model for accountancy with main topic Journal of Adaptation. In the teaching and learning accountancy the teachers are expected to be able to use various models in learning process in order that it can raise the interest of studying and the result of studying becomes higher.Key Word: Studying of Learning Cycle Model, interest, the result of studying, accountancy Mata pelajaran Ekonomi/Akuntansi adalah mata pelajaran yang sangat penting dalam kehidupan dan bagi siswa dapat menunbuhkan rasa ingin tahu, jujur, kerja keras,disiplin dan dapat menumbuhkan rasa kewirausahaan yaitu kreatif dan inovatif. Masalah yang dihadapi sekarang ini mata pelajaran Ekonomi/Akuntansi pokok bahasan Jurnal penyesuaian dipersepsikan sebagai pelajaran yang sulit bagi sebagian anak, disamping itu guru kurang maksimal dalam menerapkan model pembelajaran, sehingga kondisi ini menyebabkan siswa kurang berminat dalam belajar dan memiliki hasil belajar rendah. Penelitian ini aspek yang diteliti adalah Aktivitas Belajar siswa, minat belajar siswa, hasil belajar siswa dan respon siswa dengan penggunaan model pembelajaran Learning cycle pada pelajaran Akuntansi pokok bahasan jurnal penyesuaian. Penelitian ini merupakan penelitian tindakan kelas dengan pendekatan kualitatif. Hasil penelitian menunjukkan Aktivitas belajar siswa meningkat pada siklus I sebesar 3,20 ( kurang baik) dan pada siklus II menjadi 4( baik), minat belajar siswa pada siklus I sebesar 49,74% (cukup) pada siklus II meningkat menjadi 98,05 (sangat baik). Hasil belajar siklus I sebesar 78,96 dan siklus II meningkat menjadi 85,45, Ketuntasan saat siklus I sebesar 21% dan siklus II ketuntasan 100%. Dari hasil respon melalui angket dinyatakan 75,8% siswa setuju dan senang dengan model Learning cycle (siklus belajar) pada mata pelajaran akuntansi pokok bahasan jurnal penyesuaian. Guru diharapkan dalam pembelajaran Akuntansi dapat menggunakan variasi model-model yang lebih bervariasi sehingga menimbulkan minat belajar dan hasil belajar yang tinggi.Kata kunci: Pembelajaran model Learning cycle, Minat, Hasil Belajar, Akuntansi